Climate‐change‐driven deterioration of the condition of floodplain forest and the future for the avifauna. Issue 2 (3rd July 2013) - Mac Nally, Ralph; Lada, Hania; Cunningham, Shaun C.; Thomson, James R.; Fleishman, Erica
Abstract Aim We used models of remotely sensed estimates of forest‐stand condition (degree of die‐back) with models of avian responses to stand condition to determine how the avifauna responded to a 13‐year drought, and how the avifauna might respond to a predicted much warmer and drier climate in the next 60 years. Location Floodplain forests of the southern Murray–Darling Basin, Australia. Methods We selected 45 2‐ha locations that spanned the full range of stand condition and conducted bird surveys and rapid assessments of breeding, which involved repeated measurements over the breeding season. These values were modelled as functions of stand condition and several other on‐site predictors. We made hindcast estimates of the proportions of forest in different stand‐condition classes. We developed a trajectory of change in these proportions under the regionally downscaled estimates of climate change under the A1F1 IPCC emission scenario, which were linked with patterns of change in drier, hotter extant forests. The hindcast and projected values were coupled with the results of the statistical models for the avifauna to provide future projections for the avifauna. Results Three avifaunal variables (measures of abundance, effective species richness and total breeding score summed for all species) were strongly related to stand condition. Hindcast estimates based on the assumption of original good condition suggested that the response variables had declined by > 25% since 1750. Projected declines in the response variables from 2009 to 2070 were > 29%, while differences between 1750 and 2070 were > 58%. Conclusions Stand condition strongly influences birds, so that reliable estimates of avifaunal change can be made by using remotely sensed estimates of stand condition. Given probable changes in forest condition under climate change, we project that the prospects for these avifauna are dire under the A1F1 or more extreme emission scenarios.